The Effect of Tax Planning, Tunneling Incentives, and Foreign Ownership on Transfer Pricing : (Empirical Study on Manufacturing Companies for the Period 2019 – 2023) - Farras Alif Zakaria; Mega Metalia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the effect of tax planning, tunneling incentives, and foreign ownership on transfer pricing practices in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. Using a quantitative approach and panel data regression method, this study analyzes secondary data from the company's annual financial statements. The results of the study indicate that tax planning has a significant positive effect on the company's decision to carry out transfer pricing. Meanwhile, tunneling incentives and foreign ownership are proven to negatively affect transfer pricing, although with variations in influence that are not too large compared to other variables. This study provides an important contribution in understanding the factors that influence transfer pricing policies, which can be a reference for policy makers, company managers, and researchers in better tax management.